Geo-Congress 2020. selected papers from sessions of Geo-Congress 2020 : February 25-28, 2020, Minneapolis, Minnesota - Hambleton, James P.; Makhnenko, Roman; Budge, Aaron S. 1974- (GSP (Series) ;, 2020)
The third of seven volumes containing the full collection of papers presented at Geo-Congress 2020: Vision, Insight, Outlook. This publication contains 68 peer-reviewed papers on modeling, geomaterials, and site characterization. Topics include: computational geotechnics; soil properties and modeling; geophysical engineering; advances in geomechanics; and engineering geology and site characterization.